Priority directions and mechanisms of digital economy development in Ukraine - K.V. Shymanska; V.V. Bondarchuk (Економіка, управління та адміністрування)
The process of state formation involves the transformation of all spheres of society, including economic relations. The development of Ukraine’s digital economy is only gaining momentum and it is important to choose the right direction and tools for its formation. The digitalization of the economy occurs simultaneously at the macro level and at the micro level. It is necessary to build the digital environment of the national economy in such a way that it meets the needs not only of the state in the face of state institutions, but also of citizens and businesses. The study of the formation and development of digitalization of Ukraine's economy has shown that this process has strengths and weaknesses. The use of strengths can significantly accelerate digitalization and provide economic benefits for all participants of economic relations in Ukraine. This is facilitated by the opportunities available in our country. However, it is also necessary to work on leveling the weaknesses and take measures to minimize threats to the digitalization of the economy. The proposed digitization mechanisms can ensure the gradual introduction of digital technologies in strategic sectors of the domestic economy, which are the foundation for further digitalization process. It is necessary to create such conditions when digitalization is desirable and provides competitive advantages for business and convenience for consumers. In this case, the formation of the digital economy in Ukraine will be initiated by business and the public, which are the main beneficiaries of this process.